Rebels in Parliament: The Effects of Candidate Selection Methods on Legislative Behaviours. Issue 2 (2nd November 2021) - Sozzi, Fabio
Abstract: In this article, we concentrate on the question whether candidate selection mechanisms affect the propensity of members of parliament (MPs) to defect from party line. Literature suggests that MPs selected by more inclusive procedures (i.e. party primaries) are more likely to be rebels than legislators nominated directly by party leaders. Despite the increasing attention that scholars devote to candidate selection methods, empirical evidences are still limited and they are inconsistent, especially for as to concern the Italian case. Empirically, we focus our attention on the Democratic Party (Partito Democratico—PD) during the XVII legislature in Italy. The PD is an ideal laboratory to test whether candidate selection affects MPs' propensity to vote against party line because PD's legislators are both selected by party primaries and appointed by party leader. Our results suggest, in contrast to previous findings, that candidate selection is a strong predictor in explaining voting defection.